การรับรู้สารสนเทศของผู้รับผิดชอบโครงการอาหารกลางวันแบบยั่งยืน วิทยาลัยเกษตรและเทคโนโลยีเพชรบุรี (INFORMATION PERCEPTION BY ORGANIZERS IN THE SUSTAINABLE FOOD BANK PROJECT PHETCHABURI COLLEGE OF AGRICULTURE AND TECHNOLOGY) - พงศ์ภัสสร, สุกัญญา (Srinakharinwirot Research and Development Journal of Humanities and Social Sciences, 2015)
บทคัดย่อ การวิจัยครั้งนี้มีวัตถุประสงค์ (1) เพื่อศึกษาการรับรู้สารสนเทศของผู้รับผิดชอบโครงการอาหารกลางวันแบบยั่งยืน วิทยาลัยเกษตรและเทคโนโลยีเพชรบุรีในด้านบริหารและกระบวนการ ด้านกิจกรรมกระบวนการผลิตอาหาร ด้านกิจกรรมประกอบอาหาร ด้านปัจจัยตัวชี้วัดทางด้านสาธารณสุข ด้านปัญหาการรับรู้แหล่งสารสนเทศและด้านปัญหาประเภทสารสนเทศ (2) เพื่อเปรียบเทียบการรับรู้สารสนเทศของผู้รับผิดชอบโครงการอาหารกลางวันแบบยั่งยืนจำแนกตามตำแหน่งหน้าที่และเขตพื้นที่การศึกษา การวิจัยนี้เป็นการวิจัยเชิงสำรวจ กลุ่มตัวอย่างที่ใช้ประกอบด้วย ผู้บริหาร และครูผู้รับผิดชอบโครงการอาหารกลางวันแบบยั่งยืนในโรงเรียนสังกัดสำนักงานเขตพื้นที่การศึกษาจังหวัดเพชรบุรีจังหวัดสมุทรสงคราม และจังหวัดประจวบคีรีขันธ์ เขต 2 รวมจำนวน 196 คน เครื่องมือที่ใช้เก็บรวบรวมข้อมูล ได้แก่ แบบสอบถาม ซึ่งนำมาวิเคราะห์ข้อมูลโดยหาค่าความถี่ ร้อยละ ค่าเฉลี่ย ส่วนเบี่ยงเบนมาตรฐาน และวิเคราะห์ความแปรปรวนแบบทางเดียว ผลการวิจัยพบว่า (1) การรับรู้สารสนเทศเกี่ยวกับโครงการอาหารกลางวันแบบยั่งยืนด้านการบริหารและกระบวนการ ด้านกิจกรรมประกอบอาหาร ด้านปัจจัยตัวชี้วัดทางด้านสาธารณสุขทุกข้อ อยู่ในระดับมาก ส่วนด้านกิจกรรมกระบวนการผลิตอาหาร ด้านปัญหาแหล่งสารสนเทศและด้านปัญหาประเภทสารสนเทศมีการรับรู้ อยู่ในระดับปานกลาง (2) การเปรียบเทียบการรับรู้สารสนเทศจำแนกตามตำแหน่งหน้าที่และเขตพื้นที่การศึกษา ผลการวิจัยพบว่า ผู้รับผิดชอบที่อยู่ในตำแหน่งหน้าที่ที่แตกต่างกัน มีการรับรู้สารสนเทศ โดยรวมแตกต่างกันอย่างมีนัยสำคัญทางสถิติที่ระดับ 0.05 ในด้านบริหารและกระบวนการ ด้านกิจกรรมประกอบอาหาร ด้านปัจจัยตัวชี้วัดทางด้านสาธารณสุขและด้านปัญหาการรับรู้แหล่งสารสนเทศโครงการอาหารกลางวันแบบยั่งยืน และผู้รับผิดชอบโครงการอาหารกลางวันแบบยั่งยืนที่อยู่ในเขตพื้นที่การศึกษาต่างกัน มีการรับรู้สารสนเทศโดยรวมไม่แตกต่างกัน Abstract This research aimed (1) to study information perceived by organizers in the Sustainable Food Bank Project of Phetchaburi College of Agriculture and Technology in the areas of administration and processing, food producing process activity, cooking activity, health indicator factor and the problems of information perception about information sources and types, and (2) to compare the perception of responsible persons on the Sustainable Food Bank Project as classified by work position and educational area. This research was survey research. The 196 samples consisted of the administrators and teachers who were responsible for the Sustainable Food Bank Project in the schools under the office of educational areas in Petchaburi Province, Samut Songkhram Province, and Prachuap Khiri Khan Province Area 2. Data were collected by using the questionaires and analyzed by using frequency, percentage, means, standard deviation and one-way analysis of variance (ANOVA). The results of the research indicated that (1) information perception on the Sustainable Food Bank Project in the areas of administration and processing, cooking activity and all indicators factors of health were at the high level. In the areas of food producing process and perception problems of information sources and types, all items were at the moderate level. (2) The result of comparing the perception of information classified by position showed that responsible persons in different duties perceived and encountered problems differently, statistically significant at the 0.05 level of the administrative process, cooking activity, health indicator factor and problems of information sources perception for the Sustainable Food Bank Project. The information perception of the organizers in the Sustainable Food Bank Project in different educational areas was the same.